2012
DOI: 10.1111/j.1600-051x.2012.01904.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration employing gingival margin‐derived stem/progenitor cells: an animal study

Abstract: Gingival margin-derived stem/progenitor cells show significant periodontal regenerative potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 46 publications
3
93
0
2
Order By: Relevance
“…A bone regenerative capacity of GMSCs has been confirmed by multiple studies, as these cells were able to repair the critical size mandibular/calvarial defects in animals [11][12][13]. Moreover, the transplanted GMSCs proved a significant periodontal regenerative potential in vivo, with newly formed alveolar bone, cementum, and periodontal ligament fibers [14][15][16].…”
Section: Introductionmentioning
confidence: 75%
“…A bone regenerative capacity of GMSCs has been confirmed by multiple studies, as these cells were able to repair the critical size mandibular/calvarial defects in animals [11][12][13]. Moreover, the transplanted GMSCs proved a significant periodontal regenerative potential in vivo, with newly formed alveolar bone, cementum, and periodontal ligament fibers [14][15][16].…”
Section: Introductionmentioning
confidence: 75%
“…[62] . Likewise, Fawzy El-Sayed et al induced bilateral periodontal defects in the premolar and molar regions of a miniature pig model, showing that GMSC possessed the capability to regenerate bone, cementum and periodontal ligament [63] . Furthermore, Xu et al demonstrated that GMSC are able to migrate towards site of injury [64] .…”
Section: Resultsmentioning
confidence: 99%
“…MSCs exhibiting these properties have now been isolated from a wide range of tissues, including bone marrow, adipose tissue, fetal liver and blood, Wharton's Jelly of the umbilical cord, and dental tissues, including periodontal ligament (PDL MSC), dental pulp (DPSC), exfoliated deciduous teeth (SHED cells), and dental follicle [4,[19][20][21]. Recent studies have also described the isolation and characterization of MSCs from healthy and inflamed gingival tissue by isolation of clonogenic cells or magnet immunosorting, and this has been proposed as a potentially more abundant source of tissue for deriving autologous MSCs when compared to PDL [22][23][24]. A recent study also suggested that gingiva-derived MSCs include both neural crest-derived and mesodermally derived cells [25•].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…A range of different cell sources, including PDL MSC [54••], DPSC [55], adipose tissue [52], BMSC [57], and gingival MSC, have demonstrated the ability to increase regeneration of periodontal tissues [24]. Although these studies have not demonstrated superior results of any particular cell type over another, PDL cells were found to have superior outcomes in a study by Park and colleagues that tested the effects of autologous PDL, DPSC, and follicular stem cells on regeneration of defects extending to the root apex in a canine model [58].…”
Section: Use Of Msc For Periodontal Regeneration In Animal Modelsmentioning
confidence: 99%